2020
DOI: 10.1016/j.jcol.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on Fournier syndrome in a tertiary hospital in Jundiaí-SP from October 2016 to October 2018†

Abstract: Introduction  Fournier’s gangrene is a polymicrobial infection caused by aerobic and anaerobic microorganisms, which determine a fast and progressive necrotizing fasciitis, compromising mainly the perineal region and the genital region, being able to evolve to sepsis, multiple organ failure and death. Treatment consists of early surgical diagnosis and debridement, associated with broad-spectrum antibiotic therapy and hyperbaric oxygen therapy. Objective  Compare the most prevalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 10 publications
0
3
0
14
Order By: Relevance
“…40 One study concluded that early diagnosis combined with extensive surgical debridement, broad-spectrum antibiotic therapy and oxygen therapy, when available, are important measures to contain the rapid progression of the disease, thus decreasing the mortality rate. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 One study concluded that early diagnosis combined with extensive surgical debridement, broad-spectrum antibiotic therapy and oxygen therapy, when available, are important measures to contain the rapid progression of the disease, thus decreasing the mortality rate. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies show that HBOT reduces mortality in patients with FG. 30 33 However, other data do not support the routine use of HBOT in the treatment of FG. 34 Thus, we conducted this study to compare the evolution of patients treated with all classical measures with or without adjuvant HBOT oxygen therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Tal afecção foi relatada pela primeira vez por Baurienne, no ano de 1764, porém, nos anos de 1863 e 1864, com a publicação de 2 trabalhos, o urologista francês Jean Alfred Fournier descreveu com detalhes a patologia, que acometera o escroto e pênis de 5 homens jovens (Singh, Ahmed, Aydin, Khan, & Dasgupta, 2016), que primeiro ele chamou de gangrena idiopática fulminante (Inácio et al, 2020) (Yanaral et al, 2017) (Lima, Almeida, Góes, & Izabel, 2019) e, posteriormente, herdou seu nome em sua homenagem (Azevedo et al, 2016) (Yanaral et al, 2017).…”
Section: Introductionunclassified
“…Com a ação sinérgica dos patógenos aeróbios e anaeróbios, que compõe a flora polimicrobiana responsável pela infecção, há uma produção variada de exotoxinas e enzimas, como colagenases, heparinases, hialuronidases e estreptocinases (Inácio et al, 2020). Além disso, as bactérias anaeróbias causam agregação plaquetária e induzem a fixação do complemento, o que contribui para a coagulação e formação de microtrombos (Inácio et al, 2020). A partir desse ponto, um quadro de endarteríte obliterante se instala, desencadeando trombose vascular cutânea e subcutânea e necrose de tecidos irrigados por essa vasculatura.…”
Section: Introductionunclassified
See 1 more Smart Citation